(untitled) (Economic and Political Thought, 2016)
This article presents the main strategic tasks that Poland should take to strengthen their own security in the next 5 to 10 years. The first and particularly important task is to continue the cycle of national strategic planning. It is necessary to complete the development of basic directive and planning documents to ensure the implementation of the adopted in 2014, the new National Security Strategy, and at the same time to start another Strategic Review of National Security, starting a new cycle of planning. Six tasks concern the practical, organisational and technical strengthening Poland’s own security capabilities. These include: the consolidation of the system of national security management, building a system of strategic resilience to aggression, organizing national information security system, including the acceleration of the construction of the cyber security system, improving preparation of reserve mobilisation and reform of the National Reserve Forces, implementation of the ‘third wave’ of technical modernisation of the Polish Armed Forces – cyber-defence, unmanned systems, precision-guided weapons, launch and implementation of the National Programme for unmanned systems (flywheel of innovation for security and development). The third part of the tasks refers to activities aimed at strengthening the Poland’s external security pillars. These are measures to strengthen the North Atlantic Treaty Organisation, the strategic actions leading to the empowerment of the European Union and the development of cooperation between NATO and the EU (political and strategic response to hybrid threats) and strengthening strategic partnerships, especially the alliance with the US.